Reflexivity, methodology and contexts in participatory digital media research: making games with Latin American youth in London - Paula, Bruno de (Learning, Media and Technology, 2021)
In this paper, I intend to explore the role played by reflexivity in grounding a more critical perspective when designing, implementing and analysing participatory digital media research. To carry out this methodological reflection, I will present and discuss a recently concluded research project on young people’s game-making in an after-school programme targeting Latin American migrants in London/UK. I will pay special attention to how my subjectivities influenced planning, data generation and analysis of this programme, and to how context, lived experiences, curricular decisions and interpersonal relationships shaped the kinds of knowledge produced through this research. Findings emerging from this experience included relevant dissonances between curricular design/decisions and the use of participatory approaches in game-making, and the limitations of traditional analytical categories within the Social Sciences field (e.g., gender and intersectionality) to understanding subjectivities expressed through game-making. This study offers relevant insights into the place of reflexivity in research on digital media production by young people by highlighting its complexity and by calling for more critical and less homogenising approaches to this type of research.
_eprint: https://doi.org/10.1080/17439884.2021.1901114
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Korean Soap Operas, Telenovelas and Sci-fi Conspiracies: A Game-making Experience with Latin American Youth in London - Paula, Bruno de (Digital Culture and Education, 2021)
This paper explores a game-making programme for 14 Latin American migrants aged 13-18 in London/UK, carried out between October/2017-January/2018, where I investigated the relationships between game conventions, platforms and personal preferences in the curation of fluid identities through game production. Participants presented varying levels of affinity with games linked both to access issues and to other specific elements (e.g. perception of games in contemporary culture, gender). Questionnaires, observations, unstructured/semistructured interviews and gaming archives were employed to explore this participatory initiative and data was analysed through Multimodal Sociosemiotics. Findings remarked how shared understandings about digital games can find their way into platforms and act as “cultural-technical gatekeepers”, supporting or hindering the engagement with game-making of those often perceived as outsiders to gaming culture. This gatekeeping happens when there are “creative dissonances” between, for example, personal preferences and platforms aligned to normative/mainstream genres. These dissonances, however, can end up fostering subversive designs, contravening gaming conventions and potentially challenging traditional gaming boundaries. This insight is relevant for understanding “cultural-technical constraints” and subversive/non-mainstream game-making, especially in relation to innovation and appropriation of game-making resources/strategies by non-mainstream groups.
Number: 2
Keywords: 1-Jeux vidéo; 1-TV; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

Exploring game grammars: a sociosemiotic account of young people’s game-making practices - Paula, Bruno de (Visual Communication, 2021)
This article investigates the relationship between young people’s game-making practices and meaning-making in videogames. By exploring two different games produced in a game-making club in London through a multimodal sociosemiotic approach, the author discusses how semiotic resources and modes were recruited by participants to realize different discourses. By employing concepts such as modality truth claims and grammar, he examines how these games help us reflect on the links between intertextuality, hegemonic gaming forms and sign-making through digital games. He also outlines how a broader approach to what has been recently defined as the ‘procedural’ mode by Hawreliak in Multimodal Semiotics and Rhetoric in Videogames (2018) can be relevant for promoting different and more democratic forms of meaning-making through videogames.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Humanités numériques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

WàCOLETIVO : Broderie, couture et crochet comme art contemporain dans l'espace public - WàCOLETIVO (revue Periferias, 2019)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; _Nettoyé

Decolonizing the Camera: Photography in Racial Time - Sealy, Mark Anthony (Durham University, 2015)
This thesis argues that photography is tainted with ingrained racist ideologies that have been present since its earliest inception in 1839. It considers the act of photographing the Other as a site of Western violence, myth, fantasy and disavowal. It examines archival images through the prism of race, representation and human rights with the aim of extracting new meanings that bring the Other into focus. This is done by reading the images both against the politics of the time in which they were made and as contemporary objects at work in the political and cultural present. The thesis makes the case that photography is burdened with ideological fault-lines concerning race and rights. The fault-lines have been forged by cultural and colonial violence resulting in Western scopic regimes that have dominated and fixed the Other within an inescapable set of Western epistemologies that have been used to serve and enhance imperial perspectives on race. I argue that these perspectives are still active within the Western mindset manifest as benign acts of photographic empathy that work to ultimately bolster Western hegemonies and economies. This thesis is based on 25 years of experience as a researcher and curator of international photography exhibitions, direct research into archives in different continental settings, the presentation of papers in a variety of national and international contexts, and interviews withphotographers, curators and academics. My hypothesis is that the history of photography can only be complete if the voice of the subaltern is made critically present within it, so allowing us to engage with important political racial memory work that can help us re-read the past and reconfigure different meanings concerning history, race, rights and human recognition in the present. I argue that photography requires decolonising work to be carried out on its history. I propose that if we do not recognise the historical and political conjunctures of racial politics at work within photography and the effects on those that have been culturally erased, made invisible or less than human by such images, then we remain hemmed within established orthodoxies of colonial thought concerning the racialised body, the subaltern and the politics of human recognition.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Recherche-création; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé